1990
DOI: 10.1152/ajprenal.1990.259.2.f312
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin in experimental congestive heart failure in the anesthetized dog

Abstract: Studies were performed in anesthetized dogs to determine plasma endothelin (ET) concentrations in the presence and absence of experimental congestive heart failure (CHF) produced by rapid ventricular pacing for 8 days. These studies were also designed to determine the effect of exogenous low-dose ET upon integrated cardiorenal and endocrine function in the presence and absence of CHF. In these studies, plasma ET was significantly elevated in CHF (3.25 +/- 0.39 pg/ml) compared with normal (1.03 +/- 0.21 pg/ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…Nonetheless, neurohumoral activation is known to take place and play an important role in the progression of ventricular dysfunction (11). Specifically, activation of natriuretic and vasorelaxing factors such as ANP (9) and brain natriuretic peptide (12) may function to oppose the co-activation of local and circulating vasoconstrictive and sodium-retaining factors like norepinephrine, angiotensin II and endothelin (13). The current study is consistent with the concept that ADM which mediates its biological actions via generation of cAMP (14,15) could also play a compensatory role in CHF to enhance myocardial contractility via cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, neurohumoral activation is known to take place and play an important role in the progression of ventricular dysfunction (11). Specifically, activation of natriuretic and vasorelaxing factors such as ANP (9) and brain natriuretic peptide (12) may function to oppose the co-activation of local and circulating vasoconstrictive and sodium-retaining factors like norepinephrine, angiotensin II and endothelin (13). The current study is consistent with the concept that ADM which mediates its biological actions via generation of cAMP (14,15) could also play a compensatory role in CHF to enhance myocardial contractility via cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators 12 found that ET-1 increased plasma renin activity, but others reported that a relatively low dose of ET-1 significantly reduced it. 13 Such discrepant effects on the renin-angiotension system are probably due to the complexity of the nature of controlling renin release in vivo. It is most likely that the several control mechanisms known to play important roles in the regulation of renin release are affected by administration of ET-1, such as the macula densamediated pathway, the intrarenal baroreceptor, and possibly a direct effect of ET-1 on the juxtaglomerular cells.…”
Section: Effect Of Endothelin-1 On Glomerular Hydraulic Pressure and mentioning
confidence: 99%
“…In animal models of cardiac insufficiency, however, substantial increases in plasma endothelin-1 have been reported. 41,42 Therefore, the aim of the present study was to explore the possible contribution of endothelin-1 to hemodynamic compensation in humans, both in the short-term response to postural change and in the long-term adaptation to chronic cardiac insufficiency. Circulating levels of endothelin-1 and known neurohumoral mediators were determined at rest and during head-up tilt in normal subjects and patients with severe heart failure.…”
mentioning
confidence: 99%